“Tão rico de talento, como seus pais pobres de fortuna” Antônio Vicente do Nascimento Feitosa: um bacharel nos jornais oitocentista do Recife. - Ferreira, Isabel Cristina Miranda Feitosa (2021)
The purpose of this report is to give visibility to Antônio Vicente do Nascimento Feitosa, since his name appears discreetly in historiography. A person who, despite being poor, brown or mulatto, according to some documents, graduated in Legal and Social Sciences in the Legal Course of Olinda in 1837 and opened an office the following year, having carried out his activity until the last days of his life. He took on several public positions even though he was a mulatto. It transitioned into a society dominated by people of possession in the middle of the 19th century. In some environments, he was seen as white. He gained respect and consideration, to the point of being received by the Emperor Dom Pedro II, and was elected Provincial Deputy in 1863. Methodologically, we searched for information and documents in the college of Law archives as well as documents with family members, and we also carried out a survey based on the periodicals that circulated in Recife in the 19th century that are available in the Digital Hemeroteca of the National Library and the Cepe – Companhia Editora de Pernambuco, and especially those that Nascimento Feitosa worked when writing as an editor or collaborator and we crossed with historiographic data, considering who, although indirectly, was involved in the Praieiro revolt. This report accompanies a product in booklet format, trying to refer to the format of a newspaper, focusing on high school, history and law, students and those interested in knowing the lives of subjects who lived in the 19th century, as well as giving more visibility to Nascimento Feitosa, based on documents and photos obtained from the family collection, public archives of Pernambuco and images taken from newspapers already digitized by the National Library and by Companhia Editora de Pernambuco – Cepe.